S-VCAM-1 is an independent predictor of all-cause mortality in patients with dilated cardiomyopathy and hypokinetic non-dilated cardiomyopathy. (11th May 2021) - Lehnert, K; Gross, S; Bahls, M; Ulbricht, S; Winter, T; Nauck, M; Felix, SB; Doerr, M; Grabmaier, U
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): University Medicine Munich University Medicine Greifswald Introduction: The vascular cell adhesion molecule-1 (VCAM-1) is overexpressed in a number of different inflammatory processes on activated endothelium. This could be shown in both a mouse model for autoimmune myocarditis and in human heart tissue from patients with lymphocytic myocarditis. In addition to the tissue-bound one, a soluble isoform of VCAM-1 (s-VCAM-1) can also be detected in the blood. Higher levels have been associated with worse clinical outcome in chronic heart failure patients of different etiology and other patient groups. Purpose: Since both inflammation and fibrosis are key processes involved in the pathogenesis of dilated cardiomyopathy (DCM) and hypokinetic non-dilated cardiomyopathy (HNDC), we aimed to investigate the prognostic value of s-VCAM-1 plasma levels for survival in a large cohort of DCM and HNDC patients. Methods: The cohort comprised of patients with a primary diagnosis of DCM, defined as reduced left ventricular ejection fraction (LVEF <45%), increased left ventricular enddiastolic diameter according to HENRY score (LVEDD >117%) at time of diagnosis as well as HNDC, defined as a reduced left ventricular ejection fraction (LVEF <45%) but no increased LVEDD according to HENRY score (LVEDD < =117%). Exclusion criteria were primary valvular diseases (≥ second degree), acute myocarditis, cancer, chronic alcoholism, coronary artery disease with epicardial stenosis >50%, peripheral artery occlusive disease, known auto-immune disease and heart failure of other origins. Levels of s-VCAM-1 were measured in human plasma using an enzyme-linked immunosorbent assay (R&D Systems, USA). A Cox proportional hazard model for the association between s-VCAM-1 and all-cause mortality was adjusted for age, sex, time since symptom-onset, LVEF, kidney function (eGFR-CKDEPI), CRP and NT-proBNP. Results: A total of 334 DCM patients were included in this single-center cohort (78.4 % males) with a mean age of 54.0 years [interquartile range [IQR] 47.0, 63.2). On average time since symptom onset was 1.5 years (IQR 0.1, 1.1), LVEF 30.7 % (IQR 25, 37), LVEDD 67.1 mm (IQR 62, 72). During a median follow-up of 12.4 years (IQR 10.1, 13.9), a total of 118 (35.3 %) patients died. Multivariable-adjusted cox regression model revealed a significantly increased all-cause mortality risk with increasing levels of s-VCAM-1 (p for trend =0.039), (hazard ratio [HR] 1.00045 (Conf. Interval 1.00002, 1.00087) for VCAM increase of 1 ng/mL, for increase of 100 ng/ml HR 1.046 (Conf- interval 1.002, 1.091), for increase of 1000ng/ml HR 1.57 (Conf_interval 1.02-2.41) (Kaplan Meier survival estimates see Figure 1, median s-VCAM-1 = 664 ng/ml, IQR 515, 874). Conclusions: s-VCAM-1 predicts long-term survival in DCM patients independent of NT-pro-BNP and other risk determinants. Further research needs to evaluate whether this biomarker proves useful in monitoring and planning management of DCM and HNDC patients (e.g. more intensive management in high-risk patients).